PERKECAMBAHAN BENIH DAN KANDUNGAN FLAVONOID EKSTRAK SORGUM PADA BERBAGAI TINGKAT CEKAMAN KEKERINGAN (BPFP Universitas Bengkulu, 2025)
[SEED GERMINATION AND FLAVONOID CONTENT OF SORGHUM EXTRACTS UNDER DIFFERENT LEVELS OF DROUGHT STRESS]. Weeds are one of the major challenges in agricultural cultivation systems, as they can reduce crop productivity. One strategy to enhance the production of secondary metabolites in sorghum plants is the application of abiotic stress, such as drought. This approach not only has the potential to produce high-quality extracts but also supports the development of effective bioherbicides. This study aims to analyze the effects of drought stress on flavonoid content and the allelopathic properties of sorghum. The research was conducted from June to August 2024 in the Greenhouse of Bengkulu University, with bioassay tests performed in Pematang Gubernur, Muara Bangkahulu, Bengkulu City. The study employed a single-factor completely randomized design (CRD) using two sorghum varieties, Super 1 and Suri 4. The drought stress treatments included three levels of watering frequency: daily, once every three days, and once every five days. The bioassay was conducted using the petri dish method, where each petri dish was treated with 10 mL of sorghum aqueous extract, 25 mung bean seeds were sown, and incubation was carried out for three days. The results showed that the highest total flavonoid content was found in the Super 1 variety with watering every five days (4067.01 µg/g), while the lowest was observed in the Suri 4 variety with daily watering (2948.07 µg/g). The highest seed germination inhibition was recorded in both Suri 4 and Super 1 varieties under the five-day watering interval. These findings indicate that the Super 1 and Suri 4 sorghum varieties subjected to drought stress can serve as potential bioherbicide sources for sustainable weed management.